THE USE OF PROCESS IN MALE AND FEMALE'S TEXT STATUS OF FACEBOOK - Eli Sugiarti; Amrin Saragih (State University of Medan, 2015)
This study focused on the use of process in male and female’s text status ofFacebook. The objectives were to describe the patterns of process and to reasonsfor male and female’s use process in Facebook status. This study was useddescriptive qualitative methode because the object of the study was Facebookstatus in male and female. The sample was randomly taken from 1250 populationof Facebook users there were 329 clauses in text status.The research instrument ofthis study is documentary sheet. Technique of analyzing the data was descriptivetechnique, while the steps in analyzing the data are as follows: identyfing theclauses in Facebook status, classifying the clauses into types of process, anddescribing each process. Based on the table of the finding, it can be concluded thatmental process has the most dominant process found in Facebook status anddominant use by male. From the analysis, it is found that 127 (38.6%) materialprocess, 50 (15.1%)mental process, 122 (37.0%) relational process, 15 (4.5%)verbal process, 6 (1.8%) behavioral process, and 18 (5.4%) existential process.